The intellectual as stranger : studies in spokespersonship - Pels, Dick, 1948- (Routledge studies in social and political thought ;, 2000)
Annotation This volume uses detailed case studies to examine the ambiguous strangerhood of political intellectuals such as Marx, Durkheim, Sorel, Freyer and Hendrik de Man.